ALGEBRAIC GRAPH THEORY - NORMAN BIGGS (DELHI CAMBRIDGE UNIVERSITY PRESS, 1993)
Professor Biggs' basic aim remains to express properties of graphs in algebraic terms, then to deduce theorems about them. In the first part, he tackles the applications of linear algebra and matrix theory to the study of graphs; algebraic constructions such as adjacency matrix and the incidence matrix and their applications are discussed in depth. There follows an extensive account of the theory of chromatic polynomials, a subject which has strong links with the 'interaction models' studied in theoretical physics, and the theory of knots. The last part deals with symmetry and regularity properties.
Keywords: ALGEBRAIC GRAPH THEORY